Oral Health of Institutionalized Elderly: an integrative review (Research, Society and Development, 2022)
Objective: to review the literature about the identification of the oral health condition of elderly residents in long-term care institutions. Materials and methods: This is an integrative review of the literature conducted through a search strategy in the following databases: LILACS, MEDLINE, ScienceDirect and Web of Science. The search was consolidated using the descriptors "Oral Health", "Aged" and "Health of Institutionalized Elderly" with the Boolean operator "AND". Primary studies published from 2016, in English or Portuguese, were selected, which met the inclusion and exclusion criteria adopted and addressed the oral health conditions of the institutionalized elderly. Results: We found 17 studies: 8 articles in LILACS, 1 article in MEDLINE, 1 article in ScienceDirect and 7 articles on the Web of Science. The main oral health conditions of the institutionalized elderly were categorized as: Edentulism; Dental caries; Use and need for dental prosthesis; Lesions of the oral mucosa; and other conditions. Conclusion: It was concluded that edentulism, high caries activity and the need for dental prostheses were the main oral health conditions found in institutionalized elderly, and these conditions are generally associated with oral mucosal lesions and unsatisfactory hygiene.